2013
DOI: 10.1002/joc.3846
|View full text |Cite
|
Sign up to set email alerts
|

Trends in extreme rainfall and temperature indices in the western Thailand

Abstract: Trends in extreme daily temperature and rainfall have been analysed from 1961 to 2002 for the western Thailand (Mae Ping and Mae Klong river basins). Daily precipitation, maximum and minimum temperature data for 15 stations were analysed to calculate 21 extreme indices. The magnitude of trends was estimated using the linear regression method while its statistical significance was evaluated using the p-value at 5% significance level and Kendall-tau test. The result of the analysis depicts significant increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 13 publications
(13 reference statements)
5
29
0
Order By: Relevance
“…Warm days and warm nights (TX90p and TN90p) also increased with very high significant trend whereas cool days (TX10p) and cool nights (TN10p) decreased [13,49] with the same trend along with mild to steep slope. Similar results were found by another study of Sharma and Babel [50] for Western Thailand. In the observed period, significant increases in warm extremes (TX90p, TN90p, SU35, TR25, and WSDI) were experienced in North Thailand where reverse trend was observed in case of cold extremes (TX10p, TN10p, and CSDI) which is also favored by the negative trend of diurnal temperature range (DTR) except in Lamphun Province (Figure 2).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Warm days and warm nights (TX90p and TN90p) also increased with very high significant trend whereas cool days (TX10p) and cool nights (TN10p) decreased [13,49] with the same trend along with mild to steep slope. Similar results were found by another study of Sharma and Babel [50] for Western Thailand. In the observed period, significant increases in warm extremes (TX90p, TN90p, SU35, TR25, and WSDI) were experienced in North Thailand where reverse trend was observed in case of cold extremes (TX10p, TN10p, and CSDI) which is also favored by the negative trend of diurnal temperature range (DTR) except in Lamphun Province (Figure 2).…”
Section: Resultssupporting
confidence: 91%
“…All rainfall extremes showed insignificant trend except consecutive dry days (CDD) which was increasing with significant trend during the observed period of 1960-2010 (Table 3) in Chiang Rai and Tak provinces. Similar results were observed in another study of Sharma and Babel [50]. Except Lamphun Province, negative trends of PRCPTOT and R10 indicate that the rainfall was decreasing (Figure 2) over the study area.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Thus, an initial step for studies involving the climate change impact is the analysis of extreme indices (Sharma and Babel, 2014). Many studies, such as Aguilar et al (2005), Vincent et al (2005), Alexander et al (2006), Haylock et al (2006), Marengo et al (2009), Marengo et al (2010) have revealed that significant changes in some climate variables have taken place in the South America over the last century.…”
Section: Introductionmentioning
confidence: 99%
“…Research on this theme has demonstrated that greenhouse gas emissions (GARREAUD et al, 2009;KELLER, 2009;RUZMAIKIN et al, 2015) and other aspects of climate change are reaching the IPCC projections upper limits (EASTERLING et al, 1997;VINCENT et al, 2005;ALEXANDER et al, 2006;SILLMANN & ROECKNER, 2008;ORLOWSKY & SENEVIRATNE, 2012;CHOI et al, 2014;SHARMAA & BABELB, 2014;BARBU et al, 2015;GUAN et al, 2015;HU et al, 2015;PARAK et al, 2015;ALEXANDER, 2016 andRAO et al, 2016). In addition, the climate change key indicators are showing values beyond the natural variability in the Earth system, i.e.…”
Section: Introductionmentioning
confidence: 99%